Rare nephrostomy complication mimicking rupture of abdominal aortic aneurysm: a case report - Bangsawan, Kiwah Andanni; Irdam, Gampo Alam; Raharja, Putu Angga Risky; Darwis, Patrianef; Fachriza, Ihza; Rahman, Fakhri (Faculty of Medicine Universitas Indonesia, 2024)
Percutaneous nephrostomy (PCN) is a routine procedure in urology with up to 99% success rate and less than 6% of total complications dominated by minor cases. This was a case report of a 59-year-old male patient with an unusual major bleeding complication after PCN that mimicked a ruptured abdominal aortic aneurysm. The laparotomy exploration identified the bleeding source from the right lobar artery, thus renorrhaphy was performed. Proper visualization of anatomic layout, color Doppler imaging, and selecting a guiding method and technique could reduce bleeding complications following PCN.